Driving pressure and acute respiratory distress syndrome in critically ill patients. Issue 2 (5th September 2018) - Blondonnet, Raiko; Joubert, Elodie; Godet, Thomas; Berthelin, Pauline; Pranal, Thibaut; Roszyk, Laurence; Chabanne, Russell; Eisenmann, Nathanael; Lautrette, Alexandre; Belville, Corinne; Cayot, Sophie; Gillart, Thierry; et al.
ABSTRACT: Background and objective: Elevated driving pressure (ΔP) may be associated with increased risk of acute respiratory distress syndrome (ARDS) in patients admitted via the emergency department and with post‐operative pulmonary complications in surgical patients. This study investigated the association of higher ΔP with the onset of ARDS in a high‐risk, intensive care unit (ICU) population. Methods: This is a secondary analysis of a prospective multicentre observational study. Data for this ancillary study were obtained from intubated adult patients with at least one ARDS risk factor upon ICU admission enrolled in a previous multicentre observational study. Patients were followed up for the development of ARDS within 7 days (primary outcome). Univariate and multivariate analyses tested the association between ΔP (measured at ICU admission (baseline) or 24 h later (day 1)) and the development of ARDS. Results: A total of 221 patients were included in this study, among whom 34 (15%) developed ARDS within 7 days. These patients had higher baseline ΔP than those who did not (mean ± SD: 12.5 ± 3.1 vs 9.8 ± 3.4 cm H2 O, respectively, P = 0.0001). The association between baseline ΔP and the risk of developing ARDS was robust to adjustment for baseline tidal volume, positive‐end expiratory pressure, illness severity, serum lactate and sepsis, pneumonia, severe trauma and shock as primary ARDS risk factors (odds ratio: 1.20; 95% CI: 1.03–1.41; P = 0.02). The same results were found with day 1 ΔP. Conclusion: Among at‐risk ICU patients, higher ΔP may identify those who are more likely to develop ARDS. Abstract : The driving pressure at admission to the intensive care unit in intubated patients under controlled ventilation identifies patients with clinical risk factor(s), who develop acute respiratory distress syndrome within 7 days. See related Editorial